RENOPROTECTIVE ACTIVITY OF BERBERINE IN DIABETIC KIDNEY DISEASE: AN OVERVIEW FROM IN VITRO TO CLINICAL EVIDENCE (Vietnam Journal of Community Medicine, 2026)
Objectives: To synthesize mechanistic and clinical evidence on the renoprotective activity of Berberin in diabetic kidney disease across in vitro, animal, and human research, and to position Berberin within multimodal diabetic kidney disease care.Method: We searched PubMed, Cochrane, and major publishers (January 2010 to October 2025) for studies on Berberin and diabetic kidney disease. Eligible items included mechanistic in vitro/animal studies and human trials or systematic reviews reporting renal outcomes (e.g., albuminuria, eGFR). Data were summarized narratively.Results: Preclinical studies consistently show that Berberin activates AMPK and PGC‑1α to restore mitochondrial energy homeostasis; down‑regulates TGF‑β/Smad‑driven fibrosis; suppresses NF‑κB‑mediated inflammation; and enhances antioxidant defenses via Nrf2. Berberin also modulates the gut-kidney axis, lowering uremic toxins (e.g., TMAO, p‑cresol) linked to renal injury. Early clinical evidence suggests that add‑on Berberin can reduce urinary albumin‑to‑creatinine ratio and cystatin C in type 2 diabetes with good tolerability; small adjuvant studies in hypertensive T2DM report improvements in renal markers. However, large randomized trials with standardized formulations and kidney‑relevant endpoints remain lacking.Conclusion: Converging mechanistic data and preliminary clinical signals support Berberin as a promising adjunct to guideline‑based diabetic kidney disease therapy to target metabolic, inflammatory, and fibrotic pathways and albuminuria. High‑quality randomized trials evaluating UACR change, eGFR slope, and hard renal/cardiovascular outcomes are needed to define indications, dosing, and monitoring.
Keywords: Berberine, diabetic kidney disease, albuminuria, AMPK, TGF‑β/Smad, gut microbiota.